The Correlation between Physical Activity and Working Memory Capacity on Medical Student of Sebelas Maret University - Hernowo Setyo Utomo; Selfi Handayani; Nanang Wiyono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Physical activity affects brain structure and function through 3 common mechanisms: angiogenesis; neurogenesis; and regulation of neurotrophic factors. Working memory capacity is one aspect of brain function describing human intelligent which is affected by the structure and function of the brain. The aim of research was to prove that physical activity could affect working memory capacity. Methods: This research was a cross-sectional observational analytic. It had been done at Medical Faculty of Sebelas Maret University on July, 2014. The data was collected by using purposive sampling method. All responden had to fill questionnaire of Lie Scale Minnesota Multiphasic Personality Inventory (L-MMPI) in order to know the honesty level, International Physical Activity Questionnaire (IPAQ) to measure the level of physical activity during a week and reading span test to measure working memory capacity. The final result of restricted samples was 105. The data was analyzed by Spearman Correlation Test. Results: IPAQ score showed that 15.24% samples were in low level physical activity, 50.47% were in medium level physical activity, and 34.29% were in high level physical activity. Reading span test result were 93.33% samples were in high working memory capacity and the other 6.67% were in low working memory capacity. Both variables then examined by Spearman correlation test with p result 0.441 and r = -0.076 Conclusions: There is unsignificant statistic correlation between physical activity and working memory capacity on Medical Student of Sebelas Maret University Keywords: physical activity, working memory capacity, medical student